Neglected Primary Omental Pregnancy after Laparoscopic and Medical Treatment: A Difficult Diagnosis? - Federica Martelli; Caterina De Carolis; Carmelo Parisi; Emilio Piccione (Hindawi Limited, 2013)
The following case report describes a rare case of omental pregnancy in a fertile 34-year-old woman at 5 + 3 weeks of gestation who presented with abdominal pain. Clinical examination, vital signs, and laboratory values were within normal limits, so the woman was hospitalized and monitored. Laparoscopic exploration was performed according to the preoperative diagnosis of tubal pregnancy, but it showed normal pelvic organs. In view of the growth of the β-HCG value, a medical approach was attempted, without success. Due to hemodynamic instability, an emergency laparotomy was performed, and it showed an omental pregnancy, confirmed at the pathological examination.